What is Qualitative Research? - Hammersley, Martyn (The 'What is?' Research Methods Series, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book invites readers to explore the nature of qualitative research, and to recognise the varied and conflicting forms it can take. It examines how these contrast with quantitative work, as well as how they differ from journalism and imaginative literature. The book describes various methodological philosophies that have shaped qualitative work, as well as different types of orientation to be found within it today. It offers clear definitions of key terms and concepts, and also a detailed exploration of recent disputes among qualitative researchers, with a view to showing how differences in practice relate to underlying commitments. This book will be a vital resource for both new and experienced researchers.